Development of a Short Screening Questionnaire for Early Identification of Autism Spectrum Disorders in Serbia - Cvijetić Vukčević, Marija М.; Kovačić, Zoran M.; Stevanović, Dejan S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The selection of appropriate screening instruments and the availability of resources are among the key challenges in the identification of autism spectrum disorder (ASD). Recognizing the need for the continuous development of tools to identify this complex neurodevelopmental condition, the aim of this paper is to present the first two phases of the development of a screening tool that preceded the psychometric evaluation of a brief instrument for the early recognition of ASD in Serbia, titled “Minute for Autism”. For the purposes of this study, a literature review was conducted, followed by a content analysis of 26 screening questionnaires identified through the search. The analysis assessed content validity, examined the thematic areas covered by the questionnaires, and evaluated the alignment of the items with the diagnostic criteria of the DSM- 5 and ICD-11. By analyzing the items in the selected screening instruments, the forms of behavior and skills most frequently targeted by these tools were identified. The development of the short screening questionnaire involved selecting the most representative domains and formulating relevant items. This process resulted in a prototype intended for use by both parents and professionals working with young children. The questionnaire comprises 15 yes/no questions addressing key domains relevant to social communication and interaction, speech and language development, repetitive behaviors and interests, atypical sensory processing, and behavioral and emotional regulation. The instrument presented in this paper represents a preliminary step in the authors’ efforts to develop a brief screening tool that can be used by a broad range of professionals working with young children.
Keywords: screening; autism; assessment; early development